Electronic Properties of Tin Telluride: a First Principles Study - G. Sharma; P. Bhambhani; N. Munjal; V. Sharma; B.K. Sharma (Журнал нано- та електронної фізики)
In this paper, using the linear combination of atomic orbitals (LCAO) method, the electronic structure and ground state properties of the IV-VI semiconductor, SnTe are reported. To study the electron momentum density, autocorrelation function, the ab initio calculations are performed within the exchange scheme of Becke and the correlation energy functional of Perdew-Burke-Ernzerhof (PBE). The calculated Compton profiles are used to discuss the electronic properties of the SnTe. On the basis of equal-valence-electron-density profiles and valence-electron charge-density maps, we examined the nature of bonding in this compound. Our study suggests that SnTe shows more ionicity in comparison to GeTe, which is found to be in agreement with earlier data.